Treatment of tannery wastewater by different membrane bioreactors: A critical review - Md. Abdul Moktadir; Mysha Maliha; Fatema Tujjohra; Sajneen A. Munmun; Md. Samaul Alam; Md. Ariful Islam; Mohammed Mizanur Rahman (Environmental Advances, 2024)
A multitude of tannery wastewater (TWW) is a key challenge for the tanning industry. Developing efficient and new technology is crucial to regulate the disposal of TWW. Many scientists developed a variety of types of membrane bioreactor-based technologies to treat TWW. This study performed a critical review to understand the existing membrane bioreactor-based TWW treatment technologies. The review revealed that many studies tried to understand the removal efficiency of the membrane bioreactor-based technologies for treating TWW. The study findings depicted that scientists tried to develop various types of membrane technologies, i.e., modified membrane bioreactor (MBR), anaerobic MBR, moving bed biofilm bioreactor (MBBR) and hybrid MBBR, osmotic membrane bioreactor (OMBBR), hybrid MBR. The MBBR technologies performed better than the existing MBR techniques among the currently employed MBR. The review suggests a set of future research domains for sustainable treatment of TWW by applying MBR. In the future, the research focus could be on the development of novel biocarriers, application of 3D printing and the implementation of process simulation to enhance process efficiency and sustainability. . The review will aid scientists in enhancing their comprehension of the processes associated with different MBR treatment technologies used for treating TWW. This will, in turn, accelerate the advancement of process parameters and techniques.